Analysis of Wadiah Savings Product Marketing Strategy at Bank Syariah Indonesia KCP Aek Kanopan - Riska Suryani Tanjung; Reni Ria Armayani Hasibuan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This research was conducted using descriptive qualitative research methods. Qualitative research is a type of research whose discovery is not through statistical procedures or other forms of calculations and seeks to understand and interpret certain situations from the perspective of the researcher himself. The most important and most needed business activities today are financial and banking institutions, because the function of banking itself is an intermediation institution that plays a role in supporting the economic growth of a country. The marketing concept is the key to achieving company goals and providing expected satisfaction effectively and efficiently. In an interview conducted by the author to Customer Service, that so far customers in BSI KCP Aek Kanopan preferred to use savings with the principle of wadiah. Based on the rationale, the apprenticeship report took the title "Analysis of the Marketing Strategy of Wadiah Savings Products at the Indonesian Sharia Bank KCP Aek Kanopan".